Incidence and prevalence of multiple sclerosis in the UK 1990–2010: a descriptive study in the General Practice Research Database - Mackenzie, I S; Morant, S V; Bloomfield, G A; MacDonald, T M; O'Riordan, J (Journal of neurology, neurosurgery and psychiatry, 2014)
Objectives To estimate the incidence and prevalence of multiple sclerosis (MS) by age and describe secular trends and geographic variations within the UK over the 20-year period between 1990 and 2010 and hence to provide updated information on the impact of MS throughout the UK. Design A descriptive study. Setting The study was carried out in the General Practice Research Database (GPRD), a primary care database representative of the UK population. Main outcome measures Incidence and prevalence of MS per 100 000 population. Secular and geographical trends in incidence and prevalence of MS. Results The prevalence of MS recorded in GPRD increased by about 2.4% per year (95% CI 2.3% to 2.6%) reaching 285.8 per 100 000 in women (95% CI 278.7 to 293.1) and 113.1 per 100 000 in men (95% CI 108.6 to 117.7) by 2010. There was a consistent downward trend in incidence of MS reaching 11.52 per 100 000/year (95% CI 10.96 to 12.11) in women and 4.84 per 100 000/year (95% CI 4.54 to 5.16) in men by 2010. Peak incidence occurred between ages 40 and 50 years and maximum prevalence between ages 55 and 60 years. Women accounted for 72% of prevalent and 71% of incident cases. Scotland had the highest incidence and prevalence rates in the UK. Conclusions We estimate that 126 669 people were living with MS in the UK in 2010 (203.4 per 100 000 population) and that 6003 new cases were diagnosed that year (9.64 per 100 000/year). There is an increasing population living longer with MS, which has important implications for resource allocation for MS in the UK.